MODELING AND SIMULATION OF THERMOMECHANICAL STRESSES AND RESIDUAL STRESSES IN RESISTANCE SPOT WELDING BETWEEN TWO SHEETS OF MLPG METHOD - R. Vahdati; M. OzvAminian (مجله مدل سازی در مهندسی, 2013)
In current years, some attempts have been done to eliminate the grid of numerical solving processes. These attempts were created the groups of calculation methods which are known as meshless methods. MLPG methods are one of the efficient meshless methods in solving different problems. In this study, the MLPG meshless algorithm was used to Modeling and simulation of thermomechanical stresses and residual stresses in resistance spot welding between two sheets. In this method, a unit step function is used as a test functions in local weak-form. The Analyzed domain is divided to small subdomains with a circular shape. The numerical results of MLPG method are compared with the result of finite element method. The results of meshless method are similar to FEM simulation.